Penerapan Maqāṣid al-Syarī‘ah dalam Putusan Hakim: Analisis terhadap Keadilan Substantif di Pengadilan Agama - Abd. Rahman; Kurniati Kurniati; Zulhasari Mustafa (Lembaga Yasin AlSys, 2026)
The development of the legal paradigm from a formalistic approach toward substantive justice requires the integration of maqāṣid al-syarī‘ah into the practice of religious courts. However, the application of maqāṣid al-syarī‘ah in judicial decisions still tends to be limited and unsystematic, creating a gap between legal rulings and the community’s sense of justice. This study aimed to analyze the application of maqāṣid al-syarī‘ah in judicial decisions in religious courts and its contribution to the realization of substantive justice. This study used a qualitative approach with a literature study design focusing on document analysis of religious court decisions and scholarly journal articles. Data were collected through documentation and systematic searches of credible sources selected through purposive and snowball sampling, and were then analyzed using an interactive model with a thematic approach to identify major patterns and categories. The results showed that the application of maqāṣid al-syarī‘ah in judicial decisions was not yet uniform and was divided into three main patterns, namely implicit, partial, and explicit but not yet systematic. These variations were influenced by judges’ internal factors, limitations of the legal system, and social dynamics. The research findings also showed that the integration of maqāṣid al-syarī‘ah contributed significantly to strengthening substantive justice, particularly in increasing the sensitivity of decisions to public benefit and the protection of vulnerable groups. The conclusion of this study emphasizes the importance of strengthening methodological frameworks and operational guidelines for systematically integrating maqāṣid al-syarī‘ah into legal discovery. The implications of this study include the development of a more substantive theory of Islamic law, the enhancement of judges’ capacity, and the reform of religious court policies oriented toward public benefit.